STRATEGI PEMBELAJARAN BERDIFERENSIASI DENGAN MEDIA CLASSPOINT - MARDLIYAH, AINAUL; U.S, SUPARDI (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2024)
This study aims to analyze and develop a differentiated learning strategy by utilizing ClassPoint media in the learning process. The differentiated learning approach aims to meet the diverse learning needs of students by adjusting the methods, content, and learning media based on the level of ability, interests, and learning styles of students. ClassPoint media is used as an interactive tool that supports student engagement in learning and provides direct feedback to teachers. The results of the study indicate that the implementation of a differentiated learning strategy with ClassPoint media can increase student participation, facilitate more personalized learning, and provide effectiveness in learning evaluation. This study provides recommendations for educators to integrate interactive technology such as ClassPoint into learning strategies, in order to create an inclusive and adaptive teaching and learning process. ABSTRAKPenelitian ini bertujuan untuk menganalisis dan mengembangkan strategi pembelajaran berdiferensiasi dengan memanfaatkan media ClassPoint dalam proses pembelajaran. Pendekatan pembelajaran berdiferensiasi bertujuan untuk memenuhi kebutuhan belajar siswa yang beragam dengan menyesuaikan metode, konten, dan media pembelajaran berdasarkan tingkat kemampuan, minat, serta gaya belajar siswa. Media ClassPoint digunakan sebagai alat interaktif yang mendukung keterlibatan siswa dalam pembelajaran serta memberikan umpan balik langsung kepada guru. Hasil penelitian menunjukkan bahwa penerapan strategi pembelajaran berdiferensiasi dengan media ClassPoint dapat meningkatkan partisipasi siswa, memfasilitasi pembelajaran yang lebih personal, dan memberikan efektivitas dalam evaluasi pembelajaran. Penelitian ini memberikan rekomendasi bagi pendidik untuk mengintegrasikan teknologi interaktif seperti ClassPoint dalam strategi pembelajaran, guna menciptakan proses belajar-mengajar yang inklusif dan adaptif.